Cultura histórica e RPG : a aprendizagem histórica de estudantes de ensino médio a partir de uma experiência com o jogo O Desafio dos Bandeirantes - Silva, Caio Cobianchi da (2023)
The present thesis aims to analyze how high school students from a public school in Cuiabá produce historical meaning from the contact with the historical experiences aestheticized by the role-playing game (RPG) The Challenge of the Bandeirantes. This research is situated in the field of investigation of History Education, which seeks to know the lack of temporal orientation of students in order to provide methods, strategies and instruments necessary for the development of historical consciousness, from the production of historical narratives with meaning for their own lives. It is assumed that RPG is a cultural artifact of humanity linked to contemporary youth culture that, besides allowing young people to express their identity by addressing historical themes in its narrative, integrates itself into the available historical culture by organizing certain temporal representations. The hypothesis is that when players come into contact with this form of temporal representation, they produce historical meaning and can attain sophisticated levels of historical thinking linked to the exercise of otherness, historical empathy, and multiperspectivity. The research was divided in three stages: a) investigation of the previous ideas and lacks of temporal orientation of the young people from the relation with epistemological and substantive concepts (the latter relating to what has been called the Brazilian colonial period); b) execution of the game; c) investigation of possible changes in historical thinking. The method for analyzing the results was grounded theory, for understanding that its flexibility in categorizing the data does not conflict with the categories worked in History Education, but allows exploring them in their complexity and, in some cases, their contradiction. The results allowed us to build categories related to historical explanation and historical judgment of students, shedding light on the interrelation between both in the settings of historical narratives within historical culture.